2014
DOI: 10.1136/annrheumdis-2014-206033
|View full text |Cite
|
Sign up to set email alerts
|

Suitability Of Nitisinone In Alkaptonuria 1 (SONIA 1): an international, multicentre, randomised, open-label, no-treatment controlled, parallel-group, dose-response study to investigate the effect of once daily nitisinone on 24-h urinary homogentisic acid excretion in patients with alkaptonuria after 4 weeks of treatment

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
207
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 137 publications
(219 citation statements)
references
References 17 publications
9
207
0
3
Order By: Relevance
“…Ranganath and colleagues recently showed a similar dose-response effect of nitisinone when analysing urinary HGA excretion over a 24 h period in AKU patients. Furthermore, they found that nitisinone was well tolerated within the studied dose range (Ranganath et al 2014), which is consistent with our observations in mice. Both our data and that of Ranganath et al highlight the efficacy of nitisinone in reducing the levels of circulating HGA.…”
Section: Discussionsupporting
confidence: 81%
“…Ranganath and colleagues recently showed a similar dose-response effect of nitisinone when analysing urinary HGA excretion over a 24 h period in AKU patients. Furthermore, they found that nitisinone was well tolerated within the studied dose range (Ranganath et al 2014), which is consistent with our observations in mice. Both our data and that of Ranganath et al highlight the efficacy of nitisinone in reducing the levels of circulating HGA.…”
Section: Discussionsupporting
confidence: 81%
“…Reproducibility test was repeated after 2 week storage of DUS, with no appreciable loss compared to fresh spots (recovery 93.7-105.6%; CV ¼ 8.7%). These data and values expressed as mmol/mol creatinine (1,741 AE 541) or mmol/24 h (17.0 AE 7.4) were in agreement with those reported in the literature (Bory et al 1989;Mannoni et al 2004;Hughes et al 2014;Ranganath et al 2016). No appreciable HGA could be detected in DUS or urine samples from controls.…”
Section: Hplc Analysis Of Urines and Dus (Methods 2)supporting
confidence: 81%
“…The deposition of an "ochronotic" pigment produced after circulating HGA oxidation within the articular connective tissues causes ochronotic arthritis, a degenerative joint disease (Ranganath et al 2013;Millucci et al 2015); deposition may also occur in cardiac valves, leading to cardiovascular pathologies. Currently, there is no therapy for AKU, but a clinical trial with nitisinone is in progress (Ranganath et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A current ongoing trial looking at the suitability of nitisinone in AKU patients is looking to be very promising for reducing HGA. However, the major risk in these patients is an increase in plasma tyrosine, leading to corneal opacities and other more severe complications (Ranganath et al 2016). An absence of detectable tyrosine from the spectra in our study suggests that patients who have established ochronosis will likely not have to worry about the polymerisation of tyrosine and it binding to the already established ochronotic pigment in their tissues.…”
Section: Discussionmentioning
confidence: 99%